Hubungan komponen health belief model (HBM) dengan kepatuhan minum obat dan tingkat stress pada pasien hipertensi - Fauziah, Fauziah; Sastrawan, Sastrawan; Setiawan, Sabar; Mardani, Raden Ahmad Dedy (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Hypertension is a silent killer because sufferers often do not experience any symptoms at all. Complications can occur if hypertension cannot be controlled or remains high for a long period of time. The Health Belief Model (HBM) is a model used to describe individuals' beliefs about healthy living behaviors, so that individuals will engage in healthy behaviors, which can be preventive behaviors or the use of health facilities. Purpose: To determine the relationship between components of the Health Belief Model (HBM) and medication adherence and stress levels in hypertensive patients. Method: This observational analytical study, using a cross-sectional design, was conducted at the North Batukliang District Community Health Center in hypertensive patients. A sample of 90 respondents was used. Data collection was conducted through interviews, surveys, and questionnaires. Multiple logistic regression was used as the data analysis technique. Results: Based on the results of statistical tests on the relationship between the health belief model (HBM) and medication adherence, the p-value was 0.000 (< 0.05), with an Odd Ratio (OR) = 9.425. Respondents in the high perception category were 9.425 times more likely to adhere to medication compared to those in the low perception category. The relationship between the health belief model (HBM) and stress levels yielded a p-value of 0.002 (<0.05) and an odds ratio (OR) of 4.286, indicating that respondents in the high perception category were 4.286 times more likely to experience stress than those in the low perception category. Conclusion: There is a relationship between medication adherence and stress levels with the health belief model (HBM) in hypertensive patients at the North Batukliang District Health Center. Suggestion: For future researchers, it is hoped that the research population will be larger and come from different places. Health workers should also play a role in encouraging the prevention of hypertension in healthy individuals and treatment at health centers for individuals who are already sick. Keywords: Health Belief Model (HBM); Hypertension Patients; Medication Adherence; Stress. Pendahuluan: Hipertensi merupakan penyakit pembunuh diam-diam karena penderita sering kali tidak merasakan gejalanya sama sekali. Komplikasi dapat terjadi jika penyakit hipertensi yang tidak mampu di kontrol atau tetap terus menerus tinggi berlangsung dalam jangka waktu yang lama. Health belief model (HBM) adalah suatu model yang digunakan untuk menggambarkan kepercayaan individu terhadap perilaku hidup sehat, sehingga individu akan melakukan perilaku sehat, perilaku sehat tersebut dapat berupa perilaku pencegahan maupun penggunaan fasilitas kesehatan. Tujuan: Untuk mengetahui hubungan komponen health belief model (HBM) dengan kepatuhan minum obat dan tingkat stress pada pasien hipertens. Metode: Penelitian analitik observasional dengan rancangan cross-sectional, dilakukan di Puskesmas Wilayah Kecamatan Batukliang Utara pada pasien hipertensi. Sampel yang digunakan sebanyak 90 responden. Pengumpulan data dilakukan dengan wawancara, survei, dan penyebaran kuesioner. Teknik analisis data yang digunakan regresi logistik berganda. Hasil: Berdasarkan uji statistik pada hubungan health belief model (HBM) dengan kepatuhan minum obat, diperoleh p-value: 0.000 (< 0.05), Odd Ratio (OR) = 9.425, responden kategori persepsi tinggi memiliki peluang 9.425 kali patuh minum obat dibandingkan kategori persepsi rendah. Dan hubungan health belief model (HBM) dengan tingkat stres diperoleh p-value: 0.002 (< 0.05), Odd Ratio (OR) = 4.286, responden kategori persepsi tinggi memiliki peluang 4.286 kali mengalami stress dibandingkan kategori persepsi rendah. Simpulan: Terdapat hubungan kepatuhan minum obat dan tingkat stres dengan health belief model (HBM) pada pasien hipertensi. Saran: Bagi peneliti selanjutnya, diharapkan populasi penelitian lebih besar dan berasal dari tempat yang berbeda. Dan untuk kader supaya ikut berperan serta mendorong pencegahan penyakit hipertensi pada individu yang sehat dan pengobatan ke puskesmas untuk individu yang telah sakit. Kata Kunci: Health Belief Model (HBM); Kepatuhan Minum Obat; Pasien Hipertensi; Stres.